(untitled) (Revista de História da UEG (REVHIST), 2020)
This paper intends to give a brief historical overview about museums, exhibitions and the current expographic incursions. Despite conforming to a widely discussed subject, there is a shortage of brief, concise reports that relate the three terms. Thus, this text propose a synthetic chronological compilation of the historical journey of museums from their ancestors as the mouseion of antiquity, moving through universal exhibitions, museums and science centers to what should be expected from the museum in the 21st century, constantly relating the evolution of the museal environment and its design. Keywords: Expography. Exhibition. Museum. Historical Overview.